Metaphorical Expressions about Passion of Woman’s Life in the Novel Pegasus and Olympus at War by Kate O’Hearn - Waladdin Panggabean; Nofansyah (Faculty of Letters Universitas Balikpapan, 2023)
There are three objectives of this research; 1) to find the metaphorical expression about Passion of a woman life, 2) to find the meaning of metaphorical expression about Passion of a woman life. The theory being used in this research is Semiotics by limiting the discussion only on Peirce Triangle of Meaning/Semiosis. This theory are applied by determine and classify metaphorical expressions about Passion of woman life into 3 parts in Triangle of Meaning by Peirce. The methodoogy employed is qualitative research in which the researcher tried to present the issues descriptively. As for the data, they were collected from the text within the novel. The dialogues in the text were taken out as the primary data. From the first research question, the researcher conclude that the representament of this research is kind of Legisign, the object is symbol, and the interpretant is dicent sign/dicisign. The researcher also found that there are some illustrated of the main character in this novel, called Emily. She described as emotional, enthusiastic, uncontrollable, strong, faithful, and unaffected also dependable girl. From the second research question, the representament of this research is kind of sinisign, the object is symbol, and the interpretant is dicent sign/dicisign.